Influence of Ni60-WC Bionic Unit on the Wear Performance of 20CrMnTi Steel Prepared via Laser Cladding - Bo Cui; You Lv; Zhaolong Sun; Yan Tong (Metals)
In recent years, the field of bionic engineering has advanced at a remarkable pace. Numerous engineering challenges have been addressed through inspiration drawn from biological organisms in nature. In this paper, laser cladding was employed to fabricate a bionic unit inspired by the radial ribs of the bivalve shell surface morphology on 20CrMnTi steel, with the aim of enhancing its wear performance. The metallic powder used in the experiments was prepared by blending Ni60 alloy powder with tungsten carbide (WC) in a predetermined ratio. The WC content was maintained within a mass percentage range of 15% to 60% in the composite powder system. The microstructure and properties of the bionic unit were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), and a hardness tester, while its dry sliding wear resistance was evaluated using a block-on-ring tribometer. The influence of the WC content on the microstructure, hardness, surface roughness, and wear performance of the bionic unit was investigated. The experimental results revealed that the bionic unit exhibited a dual microstructure comprising equiaxed crystals and fine dendritic structures. The incorporation of WC induced pronounced grain refinement, while the dispersed WC particles formed effective metallurgical bonding with the Ni-substrate. A positive correlation was observed between the WC content and hardness, with peak hardness reaching 1008 HV0.2 at 60% WC. Tribological analysis demonstrated a wear mechanism transition from dominant abrasive wear to a hybrid abrasive–adhesive wear. The wear volume of the bionic unit decreased with increasing WC content, and the extent of damage was reduced.